Synthesis of TiO2 nanoparticle using sol–gel route and testing its photovoltaic performance in dye-sensitized solar cell - Shalin; Shukla S.K. (My University, 2025)
In the present work, sol–gel method is used to synthesize TiO2 nanoparticle. The characterization of the prepared TiO2 powder is done using Powder X-ray diffraction (powder XRD), Scanning Electron Microscope (SEM), Energy-Dispersive X-Ray Spectroscopy (EDS) and Ultraviolet-Visible Spectrophotometry (UV-Vis). The XRD pattern reveals formation of anatase phase TiO2. The SEM images reveal agglomeration of nanoparticles. The absorbance spectrum of TiO2 nanoparticles was observed with excitonic peaks at 327 nm and the band gap came out to be ~3.2 eV. This prepared TiO2 was tested for photovoltaic performance by using it in the Dye sensitized solar cell (FTO/TiO2/N719/KI-I2/Pt). Conversion of solar light energy to electricity was successfully done using this TiO2. The fabricated cell showed an open-circuit voltage (VOC) of 587 mV and short-circuit current density (JSC) of 5.06 mA/cm2. Maximum power (Pmax) generated was 1.912 mW/cm2 with a fill factor (FF) of 0.644 and a conversion efficiency of 1.91%. © 2016, Allerton Press, Inc.